2017
DOI: 10.1111/liv.13330
|View full text |Cite
|
Sign up to set email alerts
|

Risk of empyema in patients with chronic liver disease and cirrhosis: A nationwide, population‐based cohort study

Abstract: The present study shows that CLDC patients have an increased risk of empyema. These patients need timely monitor for the risk of empyema, particularly for those with comorbid cirrhosis, alcoholic disorder, gastrointestinal haemorrhage and ascites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Recently, an increasing number of empyema cases in RA have been identified; therefore, the association between RA and pleural empyema has been recognized [3,4]. In this study, the incidence of pleural empyema was 23.6/10,000 in RA, which was similar to certain immunocompromised conditions with preexisting pleural effusion (18.2/10,000 in cirrhosis and 23.7/10,000 in end-stage renal disease) [25,26].…”
Section: Discussionsupporting
confidence: 55%
“…Recently, an increasing number of empyema cases in RA have been identified; therefore, the association between RA and pleural empyema has been recognized [3,4]. In this study, the incidence of pleural empyema was 23.6/10,000 in RA, which was similar to certain immunocompromised conditions with preexisting pleural effusion (18.2/10,000 in cirrhosis and 23.7/10,000 in end-stage renal disease) [25,26].…”
Section: Discussionsupporting
confidence: 55%
“…The data of one million people randomly selected from the medical claims records of the NHI 2000 Registry of Beneficiary enrollees were analyzed. The LHID2000 has been successfully used innumerous studies [ 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that diabetic patients conferred a 1.71-fold increased risk of empyema thoracis without any comorbidity [21]. A series of retrospective studies showed that the hazard of developing empyema was higher for patient with diabetes mellitus than those with chronic obstructive lung disease or chronic liver disease and cirrhosis [20,22]. Gosiewski T et al found the quantity of candida in the feces of patients with diabetes was signi cantly higher compared to non-diabetic controls [23].…”
Section: Discussionmentioning
confidence: 99%